Health in developing countries - The determinants of health in Latin American and Caribbean countries - Klintberg,Fredrik (2009)
Problem discussion: There are still today many problems related to health in developing countries. When reasoning on how to deal with these problems, it is important to study the determinants of health in each country. Each country has got its own characteristics. The development process never ends, and each health care system needs to be adaptable for the ongoing changes, in order to meet local needs. In the end, it is the health care system that counts and determines the final health status of the population. Purpose: The purpose of this thesis is to study what determines health in three Latin American and Caribbean countries (Bolivia, Colombia and the Dominican Republic), how the significance of these determinants differ between the countries, and put these in relation to the design of the health care system. Method: The thesis is based on empirical facts, along with a theoretical framework on health in developing countries, and a regression analysis, based on 28 Latin American and Caribbean countries, with data from World Bank Development Indicators for the year 2006. This method covers the current situation in the Latin American and Caribbean region, with a focus on health and the health care system in Bolivia, Colombia and the Dominican Republic. Conclusion: There are many different explanatory variables for health. GDP per capita, health expenditure, and primary school enrollment are positively related to health, whereas the living in rural areas has a negative impact on health. This negative relation between health and rural living can be explained by the lack of universal health care coverage and less developed health care facilities in the rural settings. The main problem regarding health for Bolivia, Colombia and the Dominican Republic is associated with the lack of universal coverage of the population, especially the rural population, which shows a need for a more decentralized health care sector, with a focus on local individual needs.
Keywords: economic growth; poverty; Developing Countries; health determinants; health care system; Latin America; rural population; Economics, econometrics, economic theory, economic systems, economic policy; Nationalekonomi, ekonometri, ekonomisk teori, ekonomiska system, ekonomisk politik